2019
DOI: 10.4252/wjsc.v11.i8.452
|View full text |Cite
|
Sign up to set email alerts
|

Neural regeneration by regionally induced stem cells within post-stroke brains: Novel therapy perspectives for stroke patients

Abstract: Ischemic stroke is a critical disease which causes serious neurological functional loss such as paresis. Hope for novel therapies is based on the increasing evidence of the presence of stem cell populations in the central nervous system (CNS) and the development of stem-cell-based therapies for stroke patients. Although mesenchymal stem cells (MSCs) represented initially a promising cell source, only a few transplanted MSCs were present near the injured areas of the CNS. Thus, regional stem cells that are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…We also demonstrated that iSCs were present in post-stroke human brain [ 99 ] and that iSCs obtained from mouse [ 98 ] and human brains [ 96 , 97 ] differentiate into electrophysiologically functional neurons. These results indicate that factors regulating the fate of endogenous iSCs (e.g., factors promoting cell proliferation of iSCs or factors inhibiting cell death of iSCs) can facilitate neural repair and may be clinically useful in treating patients with stroke [ 100 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…We also demonstrated that iSCs were present in post-stroke human brain [ 99 ] and that iSCs obtained from mouse [ 98 ] and human brains [ 96 , 97 ] differentiate into electrophysiologically functional neurons. These results indicate that factors regulating the fate of endogenous iSCs (e.g., factors promoting cell proliferation of iSCs or factors inhibiting cell death of iSCs) can facilitate neural repair and may be clinically useful in treating patients with stroke [ 100 ].…”
Section: Findings After Early Reperfusion Under Lethal Ischemia Inmentioning
confidence: 99%
“…This study examines the ability of EOC2 microglial cells to support the viability, proliferation, neurogenesis, and survival of primary cortical cells outside of the classic neurogenic niche during homeostasis and following mechanical injury. Stem cell progenitors outside of the classic neurogenic niches have the capacity for neurogenesis during normal homeostasis and following injury or disease given exposure to the proper combination of neurogenic cues [47,[48][49][50]. Cortical microglial cells are a potential source of neurogenic signaling molecules [4,[39][40][41][42][51][52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Outside the classic neural stem cell niches, CNS stem cells have the potential to generate neurons and glial cells following ischemia or traumatic injury [35,[47][48][49][50]. Microglial-derived soluble cues are potentially important for local endogenous neurogenesis, migration, and neuronal survival [51].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cells of the adult mammalian central nervous system have destructive repair capabilities, especially the proliferation and differentiation of endogenous neural stem cells that can promote neurogenesis ( Shinozuka et al, 2014 ; Nakagomi et al, 2019 ). The endogenous neural stem cells of the adult brain are mainly present in the subventricular zone (SVZ) region of the lateral ventricle and the subgranular zone (SGZ) region of the hippocampus ( Péron and Berninger, 2015 ; Boldrini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%